EVALUATION OF THE FORMATION AND VORTEX TRACE INFLUENCE OF LIGHT UNMANNED MULTICOPTERS - V. P. Asovsky; A. S. Kuzmenko (Научный вестник МГТУ ГА)
The introduction of unmanned aerial vehicles is one of the most dynamic areas of civil aviation development over the last years. The main field of their application is the performance of different aerial works.  The most part of the aerial works is characterized by a small distance of flying unmanned vehicles from humans, animals, plants and infrastructure. Thus the influence of inductive velocities of these vehicles on the objects and some processes of aerial works is the topical issue. The article considers the problems of evaluation of vortex trace formation and description of inductive velocities field within the flying area of light unmanned multicopters which are the most popular and promising for the performance of the basic aerial works. The studies have been conducted by a numerical experiment using the software package developed in Delphi. On the bases of the defined multicopter parameters, conditions and flight modes created package provides simulation of the vortex trace formation of multicopter as a set of the mutually influencing П-shaped vortices of the multicopter rotors, graphic visualization of the vortex trace and calculations according to the inductive velocities in the flight area with the construction of the vector diagrams as well as some related problems. The article presents the graphic data on the spatial configuration of vortex trace and distribution of inductive velocities in the transverse planes which are unequally distant from the multicopter; for example,  light hexacopter "Odonata agro", for which the proximity of experimental and calculation data of drops sedimentation at aerial spraying, received with the use of the package, confirms indirectly the package adequacy as well as configurations of vortex trace which are comparable in flight weight and load upon rotors of quadcopters and octocopters. According to the calculated data the general regularities and features of the vortex trace formation and configuration, distributions of the inductive velocities within the flying area of the light multicopters are formulated in this paper. The results can be used at the evaluation of the parameters and the vortex trace influence of light unmanned aerial vehicles on the surrounding objects and optimization of rational structural designs and multiсopter flight modes while performing aerial works.